Development and Validation of an Analytical Procedure for Determining Convallatoxin in Medicinal Products Containing Cardiac Glycosides of Lily of the Valley - T. A. Golomazova; N. P. Antonova; N. E. Semenova; E. P. Shefer; S. S. Prokhvatilova (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. The safe use of lily-of-the-valley medicinal products requires adequately controlling the content of cardiac glycosides. The State Pharmacopoeia of the Russian Federation stipulates that the content of cardiac glycosides in lily-of-the-valley medicinal products should be quantified using bioassays and spectrophotometry. However, the determination of cardiac glycosides needs more accurate and selective physicochemical methods, such as high-performance liquid chromatography (HPLC).AIM. This study aimed to develop and validate an HPLC analytical procedure for the quantitative determination of cardiac glycosides (convallatoxin) in lily-of-the-valley herbal medicinal products.MATERIALS AND METHODS. The study examined the Lily-of-the-Valley Tincture, Zelenin Drops, Valocormid, Carniland®, and Lily-of-the-Valley Extract Reference Standard samples. The content of cardiac glycosides was determined by comparison with a reference standard for convallatoxin by HPLC and spectrophotometry. The samples were prepared as outlined in Monograph 3.4.0003.18 Lily-of-the-Valley Herb Tincture of the State Pharmacopoeia of the Russian Federation. Mixed cardiac glycosides were separated on a Luna 5 µm C18(2) column by gradient elution with 0.1% orthophosphoric acid in water and acetonitrile. The analysis was performed using an autoinjector with sample cooling to 5 °C.RESULTS. The developed analytical procedure met the acceptance criteria for specificity, intermediate precision, linearity (correlation coefficient of 0.99985), and repeatability (relative standard deviation of convallatoxin measurements of 1.61%). The analytical procedure is suitable for the quantitative determination of convallatoxin in lily-of-the-valley herbal medicinal products because it produces reliable and repeatable results.CONCLUSIONS. The authors developed a highly sensitive and selective HPLC analytical procedure for the quantitative determination of convallatoxin in lily-of-the-valley herbal medicinal products. The content of convallatoxin ranged from 0.012 to 0.018 mg/mL in the liquid active substance Lily-of-the-Valley Tincture, from 0.004 to 0.013 mg/mL in the medicinal product Zelenin Drops, and from 0.005 to 0.007 mg/mL in the medicinal products Carniland® and Valocormid. For the Lily-of-the-Valley Extract Reference Standard, the content of convallatoxin amounted to 0.029 mg/mL.